PERSPECTIVES OF IMPLEMENTING FOREIGN INVESTMENTS IN THE COUNTRY'S ECONOMY - Yusupova Klara Abdullayevna (European Science Publishing, 2024)
The article explores the prospects of attracting foreign investments into the national economy, highlighting their pivotal role in fostering economic growth, technological advancement, and infrastructure development. Emphasis is placed on the significance of creating favorable conditions for investors, including regulatory reforms, economic stability, and transparent governance. Additionally, the paper examines the potential impact of foreign investments on the transport sector, reflecting its importance for enhancing trade and logistics. The study aims to provide an in-depth analysis of Uzbekistan's investment climate and the benefits of expanding international cooperation in this sphere.
Keywords: Foreign investments, economic growth, infrastructure, regulatory reforms, transport sector, international cooperation, investment climate.